2011
DOI: 10.1111/j.1600-0706.2010.19311.x
|View full text |Cite
|
Sign up to set email alerts
|

Prey risk assessment depends on conspecific density

Abstract: In many systems, the number of prey killed by predators increases with prey density. Th is in turn generates higher levels of the indirect signals that prey use to assess predation risk. A model developed by Peacor (2003) showed that prey that respond to predator cues without accounting for conspecifi c density will consistently over-or under-estimate risk and therefore invest improperly in anti-predator defense. We tested this model using Rana temporaria tadpoles as prey and Aeshna cyanea dragonfl y larvae as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
44
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 22 publications
4
44
1
Order By: Relevance
“…However, as predicted by the R-AH, prey conspecific density can also affect how prey perceive and assess the actual predation risk to which they are exposed. We found that plasticity in prey behavior is affected by predation risk and that, contrary to a previous study it was not affected by prey conspecific density (Van Buskirk et al 2011). However, we also found that the tadpoles' tail width and tail muscle depth (i.e., a prey morphological traits) were affected by the interaction between predation risk and prey conspecific density, highlighting that prey can indeed estimate population density to evaluate actual levels of predation risk, supporting Peacor's (2003) R-AH.…”
Section: Discussioncontrasting
confidence: 56%
See 3 more Smart Citations
“…However, as predicted by the R-AH, prey conspecific density can also affect how prey perceive and assess the actual predation risk to which they are exposed. We found that plasticity in prey behavior is affected by predation risk and that, contrary to a previous study it was not affected by prey conspecific density (Van Buskirk et al 2011). However, we also found that the tadpoles' tail width and tail muscle depth (i.e., a prey morphological traits) were affected by the interaction between predation risk and prey conspecific density, highlighting that prey can indeed estimate population density to evaluate actual levels of predation risk, supporting Peacor's (2003) R-AH.…”
Section: Discussioncontrasting
confidence: 56%
“…However, to ensure a constant tadpole v www.esajournals.org per capita food level, we added industrial fish food daily to all mesocosms (10% of tadpole mass) according to Van Buskirk et al (2011). It is important to highlight that this procedure was conducted to minimize intraspecific competition among tadpoles.…”
Section: Experimental Design and Setupmentioning
confidence: 99%
See 2 more Smart Citations
“…Such traitmediated indirect interactions (TMIIs) are facilitated, for example, by predator cues or chemicals from crushed conspecifics (Behrens Yamada et al 1998, van Buskirk & Arioli 2002 and have the potential to induce cascading effects (Werner & Peacor 2003, Schmitz et al 2004. TMIIs are typically changes in prey behaviour, such as a reduced activity, and depend on prey density and the concentration of predator cues (van Buskirk et al 2011). Thus, prey individuals spend less time foraging to reduce their predation risk.…”
Section: Discussionmentioning
confidence: 99%